Assessing proportionality in capital cases: a case study of Ohio - Berry III, WW (2011)
When the United States Supreme Court approved the reinstatement of the death penalty in the United States in 1976, it did so based on the promise of new safeguards against comparative excessiveness and relative disproportionality resulting from jury sentencing in capital cases. As Justice Stevens noted in 2008, one of these safeguards – meaningful appellate review of death sentences – is, in practice, non-existent. This thesis examines the use of this purported safeguard by the Ohio Supreme Court, in the form of comparative proportionality review, to determine the degree to which Ohio capital cases are ‘relatively proportionate’ in the time period after the state adopted life without parole as a sentencing option in 1996. Specifically, this thesis employs two approaches to identifying ‘similar’ cases – the overall aggravation approach (through logistic regression analysis) and the fact specific approach – and then compares each death sentence to its group of ‘similar’ cases to determine whether it is relatively proportionate, given the death sentencing ratio of its comparable group. After establishing that at least forty per cent of Ohio cases were relatively disproportionate, the thesis argues that Ohio’s current approach violates the requirements of the Eighth Amendment. In particular, the Court’s failure to examine cases sentenced to life as part of its proportionality review and its use of the precedent-seeking approach has the outcome of ignoring death sentences that are comparatively excessive. Finally, the thesis concludes by offering a normative model by which Ohio can improve its administration of comparative proportionality review. The thesis advocates the use of a ‘purposive’ approach, defining ‘similarity’ on the basis of the intended purpose of punishment, and suggesting that just deserts retribution provides the best approach for determining ‘similarity’.